Perceived organizational culture and turnover intentions: The serial mediating effect of perceived organizational support and job insecurity - Salvador, Mónica (2022)
This study aims to analyze the relationship between perceived organizational culture (POC) and turnover intentions (TI) and if this relationship is mediated by perceived organizational support (POS) and job insecurity (JI). For this purpose, the following hypotheses were formulated: (1) POC (support, goals, innovation, and rules) has a negative and significant relationship with TI; (2) POC (support, goals, innovation, and rules) has a positive and significant relationship with POS (affective and cognitive); (3) POS (affective and cognitive) has a negative and significant relationship with TI; (4) POS (affective and cognitive) has a negative and significant relationship with JI; (5) JI has a positive and significant relationship with TI; and (6) POS (affective and cognitive) and JI both represent a serial indirect effect in the relationship between POC (support, goals, innovation and rules) and the TI. This study's sample includes 661 participants working in organizations based in Portugal. The results indicate that only the perception of supportive and goal culture has a negative and significant association with TI; POC has a positive and significant association with POS; POS has a negative and significant association with JI and TI; JI has a positive and significant association with TI; affective POS and JI have a serial mediation effect in the relationship between supportive and goal POC and TI; cognitive POS and JI have a serial mediation effect in the relationship between goal POC and TI. [ABSTRACT FROM AUTHOR]